Cortical activation and inter-hemispheric sensorimotor coherence in individuals with arm dystonia due to childhood stroke. Issue 8 (August 2015) - Kukke, Sahana N.; de Campos, Ana Carolina; Damiano, Diane; Alter, Katharine E.; Patronas, Nicholas; Hallett, Mark
Highlights In individuals with dystonia after childhood stroke, functionally relevant EEG abnormalities can be identified. Ipsilesional sensorimotor cortical activation in the 8–12 Hz range is abnormally reduced in patients and correlates with weakness of the more affected wrist. Resting inter-hemispheric sensorimotor connectivity in patients is abnormally reduced and correlates with increased dystonia severity and reduced hand function.